Electric Field Induced Molecular Assemblies Showing Different Nanostructures and Distinct Emission Colors. Issue 7 (8th April 2019) - Ma, Yun; Zhao, Weiwei; She, Pengfei; Liu, Suyi; Shen, Liang; Li, Xiangling; Liu, Shujuan; Zhao, Qiang; Huang, Wei; Wong, Wai‐Yeung
Abstract: Application of external stimuli in self‐assembly processes would offer greater degrees of freedom to regulate the supramolecular nanostructures and functions of self‐assembling molecules. In particular, the utilization of electric field to control molecular self‐assembly is of fundamental significance, and it contributes to the development of applications in nanofabrication and optoelectronic fields. Here, the self‐assembly of an anionic platinum complex ([Pt(tfmpy)(CN)2 ] − Bu4 N +, tfmpy = 2‐(4‐(trifluoromethyl)phenyl)pyridine) is studied in the absence or presence of an electric field. Scanning electron microscopy (SEM) and transmission electron microscopy (TEM) images demonstrate an interesting morphological transformation from rod‐like to flower‐shaped nanoaggregate structures. For rod‐like nanostructure, selected area electron diffraction (SAED) and powder X‐ray diffraction (PXRD) analysis suggest that the Bu4 N + cations are squeezed between adjacent platinum(II) complex anions, forming alternating layers of two ions. In addition, SAED result suggests that the flower‐shaped nanoaggregate is constructed by a layer‐by‐layer packing through the formation of Pt⋅⋅⋅Pt and π–π stacking interactions. Importantly, confocal fluorescence imaging shows that these two different stable assemblies possess distinct emission colors and lifetimes. This unique feature might be useful in various optoelectronic applications including data recording, anti‐counterfeiting, smart windows, etc. Abstract : The self‐assembly of an anionic platinum complex ([Pt(tfmpy)(CN)2 ] − Bu4 N + ) in the absence or presence of an electric field is studied in this work. Scanning electron microscopy (SEM) and transmission electron microscopy (TEM) images demonstrate an interesting morphological transformation from rod‐like to flower‐shaped nanoaggregate structure. Importantly, it is found that these two different stable assemblies possess distinct emission colors.